THE ROLE OF ENGLISH IN THE EDUCATION SYSTEM OF THE REPUBLIC OF KOREA AND UZBEKISTAN - Kiranova , Khafiza Uramishovna; Numonova, Dilshoda Axtamovna; Burkhanova , Mamura Gulyamovna (Innovative Development in Educational Activities, 2022)
This article is devoted to the question of what role the English language plays in the education system of the Republic of Korea and Uzbekistan as well as the analysis of language education in both countries, historical background of English language teaching and a measure taken by the government to boost language education.